1999
DOI: 10.1177/000348949910800901
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Carbon Dioxide Laser Resection of Supraglottic Carcinoma

Abstract: Between 1981 and 1994, 34 patients with squamous cell carcinoma of the supraglottis were treated by transoral carbon dioxide laser resection, 12 of them palliatively. Additional treatment included neck dissection in 21 patients and radiotherapy in 24 patients. The 3-year overall survival was 62%, and the actuarial survival 80%. The overall survival for T1 and T2 tumors was 71%, and that for T3 and T4 tumors was 47%. The overall 3-year survival for the early stages, I and II, was 88%, and that for the advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 23 publications
9
145
0
10
Order By: Relevance
“…Only the rate of gastrostomies seems to be higher in elderly patients; however, the total number of gastrostomies (five temporary; two permanent) is low. The finding that age does not affect functional outcome has been reported by Rudert et al 23 and has influenced our practice. For years, advanced age was considered a formal contraindication for external partial larynx resections.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Only the rate of gastrostomies seems to be higher in elderly patients; however, the total number of gastrostomies (five temporary; two permanent) is low. The finding that age does not affect functional outcome has been reported by Rudert et al 23 and has influenced our practice. For years, advanced age was considered a formal contraindication for external partial larynx resections.…”
Section: Discussionsupporting
confidence: 73%
“…In this group of locally advanced tumors, however, a higher number of complications can be expected. 1,23,24 During preoperative counseling, patients with voluminous tumors of the piriform sinus or the supraglottis should be informed that they are more likely to need a feeding tube and that temporary or permanent PEG, tracheostomy, or even a total laryngectomy 2 might also be required. Aspiration is a common complication after partial pharyngolaryngeal resections, 4,24,25 and a high incidence of pneumonia might had been expected in our patients because of the absence of postoperative prophylactic tracheotomies.…”
Section: Discussionmentioning
confidence: 99%
“…In open procedures, neck dissection is performed in the same surgical act, but there is yet controversy for transoral laser surgery. Classically, authors prefer to defer neck treatment and execute it as a secondstage procedure to minimize postoperative edema and the need for a tracheotomy, 11,12 but others have previously demonstrated that transoral laser surgery and simultaneous neck dissection are safe as a single-stage procedure, making recovery time shorter and assisting in early start of other therapies when needed.…”
Section: Neck Dissectionmentioning
confidence: 99%
“…15,16,19 The incidence of hemorrhage oscillated between 3 and 14%. 12,15,16,20 The incidence of postoperative hemorrhage is about equal for open supraglottic laryngectomy, SCPL-CHP, and laser microsurgery with an average between 3-14% in different studies. 12,15,20,21 However, every postoperative bleeding after endoscopic surgery in a non-tracheotomized patient is a serious and potentially life-threatening complication due to the risk of aspiration of blood.…”
Section: Complicationsmentioning
confidence: 99%
“…Lesions that extend upto the cricopharyngeal sphincter, or deeply infiltrative lesions causing an excavating ulcer are not suitable for endoscopic resection. 27 …”
Section: Glottic Cancermentioning
confidence: 99%